(untitled) (Vietnam Journal of Community Medicine, 2025)
Abstract: Nasal bone fracture is the most common type of maxillofacial septum bone, using about 40% of all maxillofacial bone songs because the tip is centrally located and protrudes significantly forward, so with other structures on the face. Objective: Evaluate the results of treatment of the main nasal bone. Subjects and methods: Including 123 patients predicted to be the main nasal horn and treated at the Department of Maxillofacial Surgery - Plastic and Cosmetic Surgery, Viet Duc Hospital from September 2022 to September 2024. Results: Patients who received nasal bone augmentation accounted for 94.31%, and patients who had bone fixation with screws accounted for 5.69%. The average hospital stay was 6.6 days. The results were good in terms of anatomy 100%, function 86.18%, and aesthetics 84.55%. The overall results after treatment were 76.42%, which is good. Conclusion: The main treatment method is closed nasal bone augmentation and bone fusion with screws and splints. Early surgery combined with specialized techniques brings good results in terms of anatomy, function and aesthetics.